Spatial and temporal variability of surface chlorophyll-a in the Gulf of Tomini, Sulawesi, Indonesia - QURNIA WULAN SARI; EKO SISWANTO; DEDI SETIABUDIDAYA; INDRA YUSTIAN; ISKHAQ ISKANDAR (Biodiversitas Journal of Biological Diversity, 2018)
Sari QW, Siswanto E, Setiabudidaya D, Yustian I, Iskandar I. 2018. Spatial and temporal variability of surface chlorophyll-a in the Gulf of Tomini, Sulawesi, Indonesia. Biodiversitas 19: 793-801. The Gulf of Tomini (GoT) is mostly influenced by seasonal and interannual events. So, the immensive aim of this study is to explore spatial and temporal variations of chlorophyll-a (chl-a) and oceanographic parameters in the GoT under the influences of monsoonal winds, El Niño Southern Oscillation (ENSO), and Indian Ocean Dipole (IOD). The data were collected from the satellite imaging of chl-a and sea and surface temperature (SST) as well as surface wind from the reanalysis data for a period of January 2003 to December 2015. Monthly variations of the chl-a and SST in the GoT reveal chl-a bloom in the center part to the mouth of the GoT during the southeast monsoon season (boreal summer). The chl-a concentrations were relatively higher (>0.1 mg m-3) and distributed throughout most of the areas near the Maluku Sea. The SST in the middle of the GoT was relatively lower than that near the Maluku Sea (the eastern part of the GoT). On the other hand, during the northwest monsoon (boreal winter), the chl-a concentration decreased (<0.1 mg m-3). During this season, the SST was relatively higher (28-29 °C) than that during the boreal summer (27-26 °C) and distributed uniformly. Meanwhile, on interannual timescale, the ENSO and IOD play important role in regulating chl-a distribution in the GoT. High surface chl-a concentration was observed during El Niño and/or positive IOD events. Enhanced surface chl-a concentration during El Niño and/or positive IOD events was associated with the upward Ekman pumping induced by the southeasterly wind anomalies. The situation was reversed during the Niña and/or negative IOD events.